Trends and evolution in Islamic social finance research: A comprehensive bibliometric study - Sudarsono, Heri; Nugrohowati, Rindang Nuri Isnaini; Mifrahi, Mustika Noor; Tumewang, Yunice Karina; Fitriyani, Yeny; Lidasan, Mussolini Sinsuat (Review of Islamic Social Finance and Entrepreneurship, 2025)
Purpose – This study provides a comprehensive overview of the current state of Islamic social finance literature using VOSviewer analysis to identify key themes, trends, and emerging areas in this field.Methodology – A bibliometric analysis was conducted using VOSviewer to map and visualize key concepts and emerging topics in the Islamic social finance literature. The analysis focuses on the term "Islamic social finance’."Findings – The analysis confirms the foundational role of traditional concepts, such as "Islamic social finance, " in the literature and identifies emerging themes, such as the impact of Covid-19 and economic crises. These findings highlight the evolution of literature and its adaptation to contemporary global challenges.Implications – This study underscores the need to explore how established concepts in Islamic social finance can be applied to address modern socioeconomic issues. The identification of emerging themes suggests potential areas for future research, particularly regarding how Islamic social finance can contribute to solving global challenges. For practitioners, the insights gained can serve as a guide for the development of Islamic financial products that are context-sensitive and align with both traditional principles and contemporary needs.Originality – This study makes a unique contribution by using bibliometric analysis to map the evolving landscape of Islamic social finance research, highlighting both established and emerging areas of interest. The findings of this study provide valuable insights for future research and practical application in this field.